Pelaporan Untuk Mengurangi Tindak Kriminal dan Non Kriminal Di Kota Mojokerto Dengan Menggunakan Metode Haversine dan Metode Multiple Criteria Utility Assessment - Antonius Wibisono; Justinus Andjarwirawan; Rudy Adipranata (Jurnal Infra, 2021)
Crime is a form of violation of the law, which always exists in society. Crime, crime, high unemployment rate that can lead to criminal action. For example, during the pandemic, there were several crimes committed, of course, for each city, it was different, Mojokerto City had a lot of criminal acts of drug use. Not only do criminal acts occur, non-criminal acts also occur, such as accidents, fires, etc. Based on the criminal and non-criminal problems that occur in society, it must have a media for reporting against criminals and non-criminals directly and quickly and can handling when many criminals are reported. So this program uses the Haversine method to see the shortest distance so that the shortest route can be created, and the Multiple Criteria Utility Assessment method to get a score for handling reporting at the same time. With this method, the reporter can see the shortest route and the estimated time between the user and the police, as well as the application with the next method when there are many reports. Then admin sees the existing weight so that he immediately takes care to reduce unwanted things.